Thermally tunable and electrically switchable solid sphere shell three-layer 3D Bragg microcavity laser based on cholesteric-liquid-crystals. (30th September 2019) - Hu, Jianyang; Xia, Chunli; Fu, Dongying; Zhang, Chi; Yao, Lishuang; Lu, Chunlian; Sun, Weimin; Liu, Yongjun
Abstract: This letter reports a thermally tunable and electrically switchable three-layer 3D Bragg resonance cavity consisting of dye-doped cholesteric-liquid-crystal (DDCLC) microdroplet, polyglycerol-2 and hollow-glass-microsphere (HGM). The whispering-gallery-mode and photonic bandgap mode can be controlled by varying the CLC refractive indices in HGM. The effects of the temperature and electric field on the peaks wavelengths were studied. The study results present the prospect of thermally and electrically controlled the output mode of the microlaser and such solid shell tunable DDCLC microsphere lasers have an outstanding potential applications in integrated microlasers, tunable optical devices and highly sensitive sensor.